2023
DOI: 10.1007/s00784-023-05375-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of two different patient decision aids in prosthodontic consultations: a prospective randomized controlled study

Silvia Brandt,
Hans-Christoph Lauer,
Jan-Frederik Güth
et al.

Abstract: Objectives Different approaches to prosthodontic consultation, all involving a strong focus on shared decision-making, were analyzed from the perspective of patients by inter-group comparisons. No patient decision aid (PDA) was used in the control group, a paper-based PDA in test group 1, and a software-based PDA in test group 2. Materials and methods Seventy-five patients were prospectively randomized to the control group or a test group. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…(5,11) Patient appreciation towards the treatment conducted has also been studied. (11) Brandt S (2) in his study emphasized that patients frequently encounter an extensive amount of information, which can be overwhelming, particularly when it comes to the options and requirements for prosthodontic treatment. https://www.indjst.org/ This epidemiological study highlighted which factors in particular affect the decision-making of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5,11) Patient appreciation towards the treatment conducted has also been studied. (11) Brandt S (2) in his study emphasized that patients frequently encounter an extensive amount of information, which can be overwhelming, particularly when it comes to the options and requirements for prosthodontic treatment. https://www.indjst.org/ This epidemiological study highlighted which factors in particular affect the decision-making of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In dental offices, patients frequently encounter an extensive amount of information, which can be overwhelming, particularly regarding the options and requirements for prosthodontic treatment. (2) It has been suggested that acceptance of new dental prostheses depends upon an individual's feelings about edentulism. (3) For a particular clinical situation regarding edentulousness, various prosthodontic treatment options are available, such as removable, fixed, and implant-supported prostheses.…”
Section: Introductionmentioning
confidence: 99%